Chapter «Ultimamente con non poco travaglio alla Cocincina si videro»: viaggiatori gesuiti in Asia orientale nel secolo XVII - Pelliccia, Carlo (Studi e saggi, 2021)
This article examines one section, Regno della Cocincina of the unpublished manuscript Ragguaglio della missione del Giappone (17th century) preserved in the Archivum Romanum Societatis Iesu (ARSI). I analyze the historical-political, socio-cultural, ethnographic, and geographical information conveyed by the report's author. The text explores the role of the Society of Jesus' correspondence in the phenomenon of cultural interaction and mutual knowledge between Europe and East Asia in the early modern era.